Methods of Applying Hermeneutics in Interpreting The Qur'an and Sharh Hadith - Ridwan, Mohammad; Deswan, Roki Ade; Afrizon, Afrizon; Iska, Syukri (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This Journal explores the application of hermeneutics as a methodological framework for interpreting the Qur'an and the exegesis of Hadith. Hermeneutics, the art and science of interpretation, offers a systematic approach to understanding religious texts by considering historical, cultural, and linguistic contexts. The study emphasizes the significance of hermeneutical principles in revealing deeper meanings and insights within Islamic texts, which are often layered and complex. The research highlights various hermeneutical strategies, including textual analysis, contextualization, and the role of the interpreter's perspective. By examining classical and contemporary interpretations, the paper demonstrates how hermeneutics can bridge the gap between traditional understandings and modern applications, making the teachings of the Qur'an and Hadith more accessible to diverse audiences, particularly in English-speaking contexts. Furthermore, the paper discusses the implications of hermeneutical approaches for interfaith dialogue and contemporary ethical issues, illustrating how a nuanced understanding of Islamic texts can foster mutual respect and understanding among different cultures and religions. Ultimately, this study advocates for a hermeneutical approach as a vital tool in the ongoing quest for knowledge and spiritual growth within the Islamic tradition.